Estimating intertemporal preferences for resource allocation - Howitt, Richard E.; Msangi, Siwa; Reynaud, Arnaud; Knapp, Keith C. (Wiley, 2005)
In this article, we show how the degree of risk aversion, discounting, and preference for intertemporal substitution for a natural resource manager can be structurally estimated within a recursive utility framework. We focus on the management of a reservoir in California, and test the data for consistency with a recursive utility model specification versus standard time‐additive separability. The results show that the data are consistent with a risk‐averse manager with recursive preferences. The data also reject time‐additive separability, with or without risk aversion, such as the standard constant relative risk aversion utility model. The improvement in model fit when recursive preferences are used is notable.